Social rank versus affiliation: Which is more closely related to leadership of group movements in Tibetan macaques (Macaca thibetana)?. Issue 8 (17th March 2016) - Wang, Xi; Sun, Lixing; Sheeran, Lori K.; Sun, Bing‐Hua; Zhang, Qi‐Xin; Zhang, Dao; Xia, Dong‐Po; Li, Jin‐Hua
Abstract : Research on leadership is a critical step for understanding collective decision making. However, only 4 of the 22 extant macaque species have been examined for the impact of social rank and affiliation on the initiation of collective movement. It is far from clear whether such impact exists and, if so, how it works among other macaques. To answer these questions, we investigated free‐ranging, Tibetan macaques' ( Macaca thibetana ) group departures from a provisioning area and tested two alternative hypotheses: personal versus distributed leadership. Personal leadership predicts that a single, highest ranking individual initiates the most group movements, whereas distributed leadership predicts that different members lead the group on different occasions and affiliative individuals have more initiations. We recorded how often and how successfully adults initiated group movements from a provisioning area into the forest, and related these variables to the duration of interindividual proximity and grooming time in the forest. All adults initiated group movements, but did so variably. Social rank was related neither to the number of successful initiations nor to the success ratio of initiations. By contrast, eigenvector centrality based on proximity relations was positively correlated with the number and ratio of successful initiations. Moreover, successful initiations were positively correlated with social grooming. Overall, Tibetan macaques showed a pattern of distributed leadership. Our study demonstrated the relationship between social affiliation and individual leadership in a macaque society. Am. J. Primatol. 78:816–824, 2016. © 2016 Wiley Periodicals, Inc.